2011
DOI: 10.1111/j.1439-0426.2010.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite fauna of native and non-native populations of Neogobius melanostomus (Pallas, 1814) (Gobiidae) in the longitudinal profile of the Danube River

Abstract: Parasite fauna of round goby Neogobius melanostomus (Pallas, 1814) in the Danube River was investigated in both its native range (two sites in the Bulgarian stretch of the Danube) and non-native range of distribution (Croatian, Slovak and Austrian stretches) during 2005 and 2006. The aim was to identify possible changes in parasite communities associated with the introduction of a host into the new environment. A total of 29 metazoan parasite species were found to parasitize round goby in the Danube River; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…Digenean trematode larvae of the species Diplostomum spp. have been observed as the most prevalent parasites in many previous studies in the Baltic Sea (Kvach & Skóra, 2006;Kvach & Winkler, 2011;Kvach et al, 2014; Table 7), as well as, other native and non-native areas (Kvach & Skóra, 2006;Kvach & Stepien, 2008;Francová et al, 2011;Gendron et al, 2012). In this study, it was found to be the most common parasite with the highest prevalence and intensity in Muuga and Mariehamn (Table 3), but absent from the two other sites.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Digenean trematode larvae of the species Diplostomum spp. have been observed as the most prevalent parasites in many previous studies in the Baltic Sea (Kvach & Skóra, 2006;Kvach & Winkler, 2011;Kvach et al, 2014; Table 7), as well as, other native and non-native areas (Kvach & Skóra, 2006;Kvach & Stepien, 2008;Francová et al, 2011;Gendron et al, 2012). In this study, it was found to be the most common parasite with the highest prevalence and intensity in Muuga and Mariehamn (Table 3), but absent from the two other sites.…”
Section: Discussionsupporting
confidence: 47%
“…Conversely, the racer goby (Babka gymnotrachelus, Kessler, 1857) has lower parasite richness in the native than in the invasive range (Kvach et al, 2014). Many previous results, in addition to the above, show that the round goby may be benefitting from decreased parasite load, supporting the enemy release hypothesis (ERH) (Kvach, 2001;Kvach & Skóra, 2006;Francová et al, 2011;Emde et al, 2012).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Data on the parasite fauna of these gobies in Central Europe have been presented by Molnár (2000Molnár ( , 2006, Francová et al (2011) and Ondračková et al (2012). Endoparasitic helminths of the Amur sleeper in the Carpathian basin were studied by Košuthová et al (2004Košuthová et al ( , 2008Košuthová et al ( , 2009.…”
mentioning
confidence: 99%
“…This species was initially reported to be specific for only Proterorhinus marmoratus (Ergens, 1967). Later on, Zosterisessor ophiocephalus, Gobius cobitis, G. niger, Neogobius melanostomus and N. fluviatilis have also been reported as hosts of G. proterorhini (Naydenova, 1974;Dmitrieva and Gerasev, 1997;Ondrácková et al, 2005;Özer, 2007;Kvach and Oğuz, 2009;Francová et al, 2011;Mierzejewska et al, 2011). Considering Proterorhinus marmoratus, a PontoCaspian relict, is the main host of this parasite species, we can speculate of its first occurrence on Pomatoschistus marmoratus in the present study is an example of the host-switching of native species of parasites on the relatively "new" host of Mediterranean origin.…”
Section: Gyrodactylidae Speciesmentioning
confidence: 99%